2013
DOI: 10.1016/j.febslet.2013.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Hsa‐miR‐125b suppresses bladder cancer development by down‐regulating oncogene SIRT7 and oncogenic long non‐coding RNA MALAT1

Abstract: Edited by Tamas Dalmay Keywords:Bladder cancer MicroRNA Hsa-miR-125b SIRT7 Long non-coding RNA MALAT1 a b s t r a c t MicroRNAs mainly inhibit coding genes and long non-coding RNA expression. Here, we report that hsa-miR-125b and oncogene SIRT7/oncogenic long non-coding RNA MALAT1 were inversely expressed in bladder cancer. Hsa-miR-125b mimic down-regulated, whereas hsa-miR-125b inhibitor up-regulated the expression of SIRT7 and MALAT1. Binding sites were confirmed between hsamiR-125b and SIRT7/MALAT1. Up-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(125 citation statements)
references
References 21 publications
3
121
1
Order By: Relevance
“…In recent years, emerging studies have been performed on SIRT7 and provided some potential mechanisms for SIRT7 in promoting cancer development. Researches in hepatocelluar carcinoma and bladder cancer indicated that SIRT7 promoted cancer cell proliferation and was regulated by microRNA, such as miR-125a-5p and miR-125b; a research in colorectal cancer identified that SIRT7 functioned as an oncogene by activation of RAF-MEK-ERK signaling pathway and increased cancer cells motility by epithelial-tomesenchymal transition (EMT) (Han et al, 2013;Kim et al, 2013;Yu et al, 2014). However, the level of SIRT7 in ovarian malignancies and the corresponding consequences of its aberrant regulation have not been discovered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, emerging studies have been performed on SIRT7 and provided some potential mechanisms for SIRT7 in promoting cancer development. Researches in hepatocelluar carcinoma and bladder cancer indicated that SIRT7 promoted cancer cell proliferation and was regulated by microRNA, such as miR-125a-5p and miR-125b; a research in colorectal cancer identified that SIRT7 functioned as an oncogene by activation of RAF-MEK-ERK signaling pathway and increased cancer cells motility by epithelial-tomesenchymal transition (EMT) (Han et al, 2013;Kim et al, 2013;Yu et al, 2014). However, the level of SIRT7 in ovarian malignancies and the corresponding consequences of its aberrant regulation have not been discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Another study proposed that SIRT7 can promote cell survival by suppressing ER stress in a myc-dependent mannner (Shin et al, 2013). In addition, evidence has suggested that SIRT7 was related to maintenance of cellular transformation in malignancies, such as breast, liver, bladder and colorectal cancer; it has an elevated level in cancerous tissues compared with the noncancerous and its levels are associated with tumor progression (Ashraf et al, 2006;Han et al, 2013;Kim et al, 2013;Yu et al, 2014). On the contrary, a comprehensive research on the expression level of SIRT7 in head and neck squamous cell carcinoma showed a significant down-regulation (Lai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in bladder cancer, miR-125b inhibited cell proliferation and motility, and enhanced cell apoptosis by regulating the expression of nicotinamide-adenine dinucleotide-dependent protein deacetylase sirtuin-7 and matrix metalloproteinase-13 (22,28). Furthermore, miR-125b decreased bladder cancer cell colony formation efficiency in vitro and the development of tumors in nude mice by targeting transcription factor E2F3 (18).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-9 may target AGO2-mediated regulation of MALAT-1 in the nucleus (67). Han et al hypothesized that Hsa-miR-125b is downregulated in bladder cancer compared with matched normal urothelium (68). However, sirtuin (SIRT)7 and MALAT-1 were upregulated in bladder cancer compared with matched normal urothelium.…”
Section: Malat-1 and Epigenetic Regulationmentioning
confidence: 99%